Investigating the Relationship Between Self-Regulation, Environmental Literacy, and Students' Problem-Solving Skills in Environmental Pollution - Oetari, Feni; Komala, Ratna; Sigit, Diana Vivanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
The environmental issues that occur could be addressed, one of which was through environmental education applied within the concept of biology regarding environmental pollution. This research aimed to determine the relationship between self-regulation and environmental literacy with problem-solving abilities regarding environmental pollution among high school students. The research method used was descriptive with a cross-sectional survey technique. The sample of this study consists of 150 high school students. The instruments used in this study were tests and questionnaires. The results of the hypothesis test showed a positive relationship between self-regulation and environmental literacy with problem-solving abilities in addressing environmental pollution, both partially and collectively. Based on the research findings, the ability to solve environmental pollution issues among high school students could be improved through self-regulation and environmental literacy. The relationship between self-regulation and environmental literacy collectively contributes to problem-solving ability, so if self-regulation and environmental literacy were high, it was expected that the problem-solving ability regarding environmental pollution among high school students will also improve, thereby providing beneficial actions in the form of prevention and resolution of contemporary environmental problems.